A comparative study of target reliability index derivation for reinforced concrete structures governed by serviceability limit state. (18th November 2018) - Lenner, Roman; Viljoen, Celeste; van Nierop, Stacey
Abstract : Typical design of reinforced concrete structures is governed by the ultimate limit state (ULS), while serviceability limit state (SLS) is checked. The target reliability index for ULS is recommended based on cost optimization and back calibration of existing practice. Many design cases, such as prestressed concrete, are, however, governed by serviceability conditions and the background for the current recommendations for target reliability index of irreversible SLS as provided by ISO 2394 is unclear. This contribution reviews previously developed generalized framework for determination of SLS target reliability by taking into account a cost ratio and statistical parameters of action‐resistance variable. Target reliability index β t, SLS can be then obtained from the previously introduced table with a minimum effort. A case‐specific approach to the cost optimization with FORM analysis is introduced in order to validate the results of the generic approach. It is found that there is a discrepancy in terms of the obtained value of target reliability index. This can be attributed to the influence of the decision parameter d in the cost optimization process. It affects the probability of failure p f ( d ) at the different rates for different formulations of SLSs. The nearly linear assumption in the generic formulation may not necessarily apply in other cases, and care should be taken when specifying target reliability index β t, SLS as the effectiveness of the decision parameter must be observed.